Clinical profile of patients before and after a diabetes reversal program in Ecuador: Perfil clínico de pacientes antes y después de un programa de reversión de diabetes en Ecuador - Albuja Chaves, Marco (2021)
Introduction. Chronic non-communicable diseases (NCDs) are the main cause of death in Ecuador and the world, and within them diabetes mellitus is one of the fastest growing morbidity and mortality. Objective. To determine if there are differences between the clinical characteristics before and after a diabetes reversal program in Ecuador. Methods. Comparative study before and after in the same individual. Patients who voluntarily entered an outpatient clinical program based on Lifestyle Medicine were followed for 8 weeks, measures were taken at the beginning and at the end of this period, which included plant-based nutrition, physical exercise and psychological support. Results. Eight patients were analyzed between 40 and 74 years (3 women and 5 men) The comparative analysis before and after the intervention showed significant differences for: Weight (p = 0.007), BMI (p: 0.004), Glucose (p = 0, 04), glycosylated hemoglobin (p = 0.007), triglycerides (p = 0.04), urea (p = 0.004), and TGP (p = 0.023). Conclusions. There is an improvement in the variables measured after having carried out the “Lifestyle Medicine” reversal program compared to the initial measurements.